The Moderating Role of Financial Literacy on the Influence of Entrepreneurial Competence on the Performance of Micro, Medium, Small Enterprises (MSME) in Buleleng Regency - Mulyani, Komang Dewi; Suwena, Kadek Rai (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine the moderating role of financial literacy on the effect of entrepreneurial competence on MSME performance. The population in this study comprises 66,368 MSME units in Buleleng Regency. The sample size was determined using Slovin’s formula with a margin of error of 10%, resulting in a total of 100 MSMEs. Samples were selected using purposive sampling with the criterion that the MSMEs must have employees. The respondents in this study were MSME owners in Buleleng Regency. Data was collected using a questionnaire with a Likert scale ranging from 1 to 5. The data analysis technique employed was Structural Equation Modeling - Partial Least Squares (SEM-PLS), using the SmartPLS version 3 software. The results of this study indicate that both entrepreneurial competence and financial literacy have a significant effect on MSME performance. Furthermore, financial literacy strengthens the significant effect of entrepreneurial competence on MSME performance